Ethical considerations for informed consent in infertility research: The use of electronic health records - Wells, Kristen J. (Adv Med Ethics, 2015)
The growing use of electronic health records (EHRs) in healthcare provides rich opportunities for biomedical research. Using EHRs, massive quantities of patient data can be extracted for research without the need to recruit patients, schedule study visits, or rely on self-reporting. However, this innovation poses significant concerns about patient privacy and confidentiality of data. Patients receiving infertility treatment may be particularly vulnerable to data breaches, as their EHRs often include sensitive health information about themselves, their partner, and their offspring. Helping patients with infertility to make informed decisions about sharing data is crucial, yet little is known about best practices for obtaining informed consent to use EHR data for research. This commentary reviews possible options for obtaining informed consent for EHR use among patients seeking fertility services. In addition, this commentary summarizes the limited research available on patient preferences for informed consent practices.